Peran Guru dalam Menstimulasi Permainan Engklek Tradisional Meningkatkan Kemampuan Motorik Kasar Anak Kelompok B di TK YPK Pniel Malawele - Meilin Anatasya Urboy; Septia Nurul Wathani; Harmaman Harmaman (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to explore the role of educators in enhancing the gross motor skills of children in Group B at TK YPK Pniel Malawele. The research adopts a qualitative methodology, utilizing techniques of data collection, presentation, and analysis. Out of ten (10) children involved in traditional engklek games, nine (9) were found to be at the expected developmental level (BSH), while one child excelled at a very good developmental level (BSB). The absence of results indicating categories of not developing (BB) or beginning to develop (MB) led to the conclusion that traditional engklek games have the potential to improve the gross motor skills of children at TK YPK Pniel Malawele in Sorong Regency, Southwest Papua Province, through activities such as jumping, throwing, and maintaining balance.